The ‘Workflow Librarian’ Reaching library users where they are - Hayes, Matthew (Institutional Knowledge at Singapore Management University, 2021)
How do libraries add value for patrons increasingly working outside library-preferred workflows (e.g. searching via Google Scholar), and accessing the library’s collection off-campus? This is a question of profound relevance to all library stakeholders – librarians, publishers, and patrons alike – and one that must be addressed to maintain mission relevance. It will mean finding new ways of service delivery and service provision that support learning and research not just remotely, but outside library-preferred workflows. It will mean putting the library ‘in the life of the user’ by designing library services that ‘surface content in the places where users actually are rather than where libraries would like them to be’ (Pinfield et al., 2017, 28). This session will explore this topic using insights from a new, large-scale survey of librarians and patrons. It will begin with ten-minute presentations from each of the four speakers outlining their perspectives on this topic. This will be followed by a thirty-minute, moderated audience Q&A structured through a series of themes, such as: the latest trends in patron behavior the practicalities and challenges of inserting the library into user workflows the relevance to the library’s mission and strategic priorities. The Q&A will balance audience participation with panel perspectives to ensure a lively discussion on this timely topic.